Design and Implementation of a Responsive Web-based System for Controlling the Financial Budget of Universities - Ahmed, Ayah; Mohammed, Chira; Ahmad, Akeela; Abdulrazzaq, Maiwan (Universitas Dinamika, 2023)
The management of the financial budget of universities is an extremely complex task due to having numerous different documents and calculation processes. In many developing regions and countries including the Kurdistan Region of Iraq, budget execution and accounting processes are manual. This had deleterious effects on the functioning of their expenditure and income management. This research represents the design and implementation of a responsive web-based system for controlling the financial budget of universities. This system can improve the recording and processing of financial transactions. Moreover, it traces all the stages of the transaction processing from budget releases, does auditing, and accounting of expenditures, incomes, deposits, and funds. Furthermore, it provides financial information on present and past performance. The system is a responsive web-based system, which adjusts the layout of the pages based on the screen size and orientation of the user's device. The system was implemented by using programming languages such as HTML, PHP, JavaScript, jQuery, AJAX, and MySQL. Finally, the provided system needed to be investigated from the performance point of view. Therefore, a questionnaire was used to determine the system’s usability by using the System Usability Scale (SUS) tool. The results revealed that a score of 86.250% of satisfaction has been achieved.